Meet Me in Pervert Park: Epistemology, Positionality, and Praxis in the Queer History of Policing and the Law. (November 2022) - Maynard, Steven
Abstract : Just a stone's throw from the campus of the university in Kingston, Ontario, where I teach, is a small park. Hugging a rocky stretch of Lake Ontario shoreline, Macdonald Park, named after Canada's first prime minister, is better known by locals as "Pervert Park." Since at least World War II, Pervert Park has been the primary cruising ground in Kingston for men searching for sex with other men, a meeting place for a mix of mostly working-class men, men stationed at the nearby military base, and the occasional intrepid university student. For women, the park's name references a different kind of pervert and signals the potential danger of walking alone in the park at night. Two of the park's main features are the Newlands Pavilion, a bandstand built in 1896, and the Richardson bathhouse, which is really a public washroom and changing facility, and which, when it first opened in 1919, boasted lockers, hot-water showers, and a list of "rules that would be enforced to maintain decorum in the bathing house." A paved path, punctuated by park benches, connects the pavilion and bathhouse, which, after dark, conveniently becomes an oval track for men cruising around and sometimes having sex behind the pavilion and bathhouse.